Formulation of Onggok Composite Flour Snack Bar (Manihot Esculenta) as Emergency Food Source of Protein - Murdiani Murdiani; Nurbani Kalsum; Sarono Sarono (AIBPM Publisher, 2022)
ABSTRACTThis study aimed to develop a snack bar product made from composite flour of Onggok and tapioca as an alternative emergency food and protein source. Additionally, to analyze the chemistry of a snack bar product made from Onggok composite flour. The study was arranged in a Completely Randomized Design (CRD) with 6 treatments and was repeated 3 times, that was the ratio of onggok composite flour and wheat flour. The ratio of onggok composite flour and wheat flour composition consisted of six levels, they were F1 (50%:50%), F2 (60%:40%), F3 (70%:30%), F4 (80%:20%), F5 (90%:10%), F6 (100%:0%). Then the data was processed by using ANOVA (Analysis of Variance) and continued with the LSD test (Least Significant Difference) at a significant level of 5%. The results of the proximate analysis showed that the protein of the snack bar was 11.06%, the dietary fiber was 8.23%, the ash content was 1.24%, and the moisture content was 3.27%. Based on the organoleptic test, it showed that the preferred level of consumer satisfaction was F1 with a ratio of 50%:50%. Therefore, the Onggok composite flour snack bar is good to use as an alternative high protein emergency food that deserves to be developed.Keywords: Onggok Composite Flour, Snack bar, Emergency foo